Stochastic mean square exponential synchronisation of time-varying complex dynamical networks via pinning control. Issue 11 (18th August 2017) - Wang, Xin; Liu, Xinzhi; She, Kun; Zhong, Shouming; Shi, Kaibo
ABSTRACT: This paper investigates the problem of stochastic mean square exponential synchronisation of complex dynamical networks with time-varying delay via pinning control. By applying the Lyapunov method and stochastic analysis, criteria on mean square exponential synchronisation are established under linear feedback pinning control and adaptive feedback pinning control, which depend on the time-varying delay and stochastic perturbation. These results complement and improve the previously known results. Two numerical examples are given to illustrate the effectiveness and correctness of the derived theoretical results.